Poultry feedstuffs [ supply, composition and nutritive value - Boorman, K. N.; McNab, J. M. (Poultry science symposium series, 2002)
This volume presents the proceedings of the 26th Poultry Science Symposium, held in Peebles, Scotland. Dealing with all aspects of feedstuffs, the papers have been written by international authorities.